Bishops, war, and canon law: The Military Activities of Prelates in High Medieval Norway. - Taylor, Louisa (Scandinavian Journal of History, 2020)
From around 1130 to 1240, Norway was troubled by a series of internal conflicts and succession disputes. In this article, I explore one element of Norwegian prelates' conduct during this period which has received little attention: their involvement in military activities. By comparing how prelates are shown to behave during periods of military conflict in the kings' sagas with the ideal mode of behaviour set out in canon law, instructional treatises, and papal letters, I explore the extent to which clerical involvement in military activities was considered acceptable in Norway across the high medieval period. I conclude that although it was considered ideal for clerics to eschew involvement in violent conflict, some direct participation in military activities was tacitly accepted within high medieval Norway. This role was limited, however, by the belief that the clergy should not shed blood or bear arms. Although there is some suggestion in sources for mid-13th-century Norway that prelates became less involved in military affairs across this period, there is little evidence that attitudes within Norway towards clerical participation in war had significantly shifted by the conclusion of the so-called 'civil war' period.